2001
DOI: 10.1080/15017410109510765
|View full text |Cite
|
Sign up to set email alerts
|

Coping with chronic pain: In‐depth interviews with children suffering from Juvenile Chronic Arthritis

Abstract: This study examined from the perspective of children with Juvenile Chronic Arthritis, their experiences of coping with chronic pain in daily life. In-depth interviews were conducted with 22 children (6-17 years). The grounded theory method was applied for analysing the taped and transcribed interviews. Seven descriptive categories were grounded in the data, labelled (1) "controlling strategies", (2) "avoidance strategies", (3) "cognitive strategies", (4) "compliance with the treatment", (5) "seeking social sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 25 publications
4
28
0
Order By: Relevance
“…This might affect their developmental process. Our study focused on chronic pain as disturbed order and, in line with a recent study by Sällfors et al . (2001), the pain affected children suffering from JCA negatively and made them different from the norm.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…This might affect their developmental process. Our study focused on chronic pain as disturbed order and, in line with a recent study by Sällfors et al . (2001), the pain affected children suffering from JCA negatively and made them different from the norm.…”
Section: Discussionmentioning
confidence: 71%
“…The background to our study was the clinical impression that children's body language shows something more about the pain experience than what parents and healthcare professionals are told. A recent qualitative study by Sällfors et al . (2001) indicated that not only the pain and the chronic disease but also coping strategies used to reduce pain affect these children negatively and made them different from their healthy peers.…”
Section: Introductionmentioning
confidence: 99%
“…Ungerer and colleagues (1988) have pointed out the social consequences of arthritis for teenagers, compared with younger children. The results of our earlier studies clarify that those children's (6Á17 years) interpersonal relations are negatively affected by pain associated with chronic arthritis (Sällfors et al, 2001(Sällfors et al, , 2002. In addition to increasing developmental challenges, pain and illness create additional challenges related to coping for teenage girls with chronic arthritis.…”
Section: Discussionmentioning
confidence: 92%
“…Pain and illness are experienced as endless and unpredictable and result in limited participation in daily life, as previously described by Sällfors et al (2001Sällfors et al ( , 2003. Compared with results of earlier studies (Sällfors et al, 2001(Sällfors et al, , 2003, where even younger boys and girls participated, the female participants in the present study have developed more effective coping strategies as being active and well-educated consumers. In addition, the teenage girls have achieved a greater maturity concerning making decisions related to treatment and therapy processes than their peers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation